2016
DOI: 10.3389/fphys.2015.00418
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Mobilization from Lipid Droplets Sustains the Anti-Steatotic Action of Iodothyronines in Cultured Rat Hepatocytes

Abstract: Adipose tissue, dietary lipids and de novo lipogenesis are sources of hepatic free fatty acids (FFAs) that are stored in lipid droplets (LDs) as triacylglycerols (TAGs). Destiny of TAGs stored in LDs is determined by LD proteomic equipment. When adipose triglyceride lipase (ATGL) localizes at LD surface the lipid mobilization is stimulated. In this work, an in vitro model of cultured rat hepatocytes mimicking a mild steatosis condition was used to investigate the direct lipid-lowering action of iodothyronines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…In animals receiving a high-fat diet (HFD), T2 prevented both adiposity and body weight-gain by increasing lipid mobilization and hepatic beta-oxidation (Lanni et al, 2005 ; de Lange et al, 2011 ; Moreno et al, 2011 ; Grasselli et al, 2012 ), accompanied by increased expression of peroxisome proliferator-activated receptor α (PPARα) (de Lange et al, 2011 ). Moreover, in vitro , it has been shown that both T2 and T3 were able to reduce excess fat storage and to mobilize triglyceride from lipid droplets in primary cultures of rat hepatocytes overloaded with lipids (Grasselli et al, 2011 , 2015 ). In contrast to T3, T2 also decreased hepatic lipogenesis in HFD-fed rats (de Lange et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In animals receiving a high-fat diet (HFD), T2 prevented both adiposity and body weight-gain by increasing lipid mobilization and hepatic beta-oxidation (Lanni et al, 2005 ; de Lange et al, 2011 ; Moreno et al, 2011 ; Grasselli et al, 2012 ), accompanied by increased expression of peroxisome proliferator-activated receptor α (PPARα) (de Lange et al, 2011 ). Moreover, in vitro , it has been shown that both T2 and T3 were able to reduce excess fat storage and to mobilize triglyceride from lipid droplets in primary cultures of rat hepatocytes overloaded with lipids (Grasselli et al, 2011 , 2015 ). In contrast to T3, T2 also decreased hepatic lipogenesis in HFD-fed rats (de Lange et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrated that the direct hypolipidizing effect exerted both by 3,5-T2 and T3 on the hepatic cells can occur even in the absence of TRs [264,265,282] and are based on the ability to activate pathways affecting TAG deposits within LDs and to promote mitochondrial oxidation and/or exocytosis of the very low density lipoproteins (VLDL) [284]. The 3,5-T2-mediated effects in steatotic hepatocytes in culture also include the recruitment to LDs of the adipose triglyceride lipase (ATGL), which might be an early mediator of iodothyronine action [282,285]. However, it has been also reported that neither T2 nor T3 increased AMPK-mediated phosphorylation of ATGL, while, on the basis of a metabolomics analysis, lipophagy (i.e., autophagy of lipids) seemed to be the major mechanism at work for triglyceride digestion, at least in the first phase of hepatic adaptation to HFD [286].…”
Section: The 35-t2 and Lipid Metabolismmentioning
confidence: 99%
“…3,5-T2 and T3 reduce the number and average sizes of lipid droplets, thus making stored triglycerides (TGs) more accessible to enzymes acting on the catabolism/secretion of free fatty acids. More recently, 3,5-T2 has been shown to reduce lipid excess in fatty hepatocytes by recruiting triglyceride lipase on the lipid droplet surface ( 44 ). 3,5-T2 also reduces lipid content and triggers phosphorylation of Akt in an insulin receptor-independent manner when incubated with NAFLD-like rat primary hepatocytes ( 45 ).…”
Section: In Vitro Studiesmentioning
confidence: 99%